1997
DOI: 10.1021/jo970290a
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Addition of 2-Furyllithium and 2-Thiazolyllithium to Sugar Nitrones. Synthesis of Carbon-Linked Glycoglycines

Abstract: A route to epimeric carbon-linked glycoglycines that exploits the stereoselective addition of 2-lithiofuran and 2-lithiothiazole to sugar nitrones has been described. The reaction occurs with opposite diastereofacial selectivity depending on whether the free nitrone or the diethyl aluminum chloride precomplexed derivative is employed. The resulting furyl or thiazolyl hydroxylamines are dehydroxylated to amines by the action of titanium(III) chloride. From these compounds the amino acids are revealed by the oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 34 publications
(21 reference statements)
0
33
0
Order By: Relevance
“…[28] In addition, we have also demonstrated that furyllithium adds stereoselectively to α-alkoxy nitrones to give furfurylhydroxylamines, which can be further converted into the corresponding α-amino acids. [29,30] Addition of furyllithium to the nitrone 2 (Scheme 3) in THF at 0°C afforded only one product (by HPLC and NMR analyses), in 73% chemical yield and with total stereoselectivity. Although it displayed spectral and analytical data in agreement with those of an addition product as desired, its relative stereochemistry was not easily identifiable.…”
Section: Introductionmentioning
confidence: 99%
“…[28] In addition, we have also demonstrated that furyllithium adds stereoselectively to α-alkoxy nitrones to give furfurylhydroxylamines, which can be further converted into the corresponding α-amino acids. [29,30] Addition of furyllithium to the nitrone 2 (Scheme 3) in THF at 0°C afforded only one product (by HPLC and NMR analyses), in 73% chemical yield and with total stereoselectivity. Although it displayed spectral and analytical data in agreement with those of an addition product as desired, its relative stereochemistry was not easily identifiable.…”
Section: Introductionmentioning
confidence: 99%
“…This compound was proved to be identical in all respects (NMR spectra and optical rotation value) to known (2S)-N-Boc-C-galactosylglycine methyl ester previously synthesized in our laboratory. [11] Next, following the above optimized cyclocondensation protocol, also the C-ribosyl formaldehyde [8] 2 was effectively transformed (see Table 1) into the corresponding 4-(C-ribosyl)-b-lactam (3R,4S)-4a (Scheme 1). The structure of this product was established by X-ray crystallography of the C3-OH-free derivative (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, aldehyde 28 was subjected to the same methodology to furnish α-aminoaldehyde 29 which was further transformed into the aza sugar D-nojirimycin (Scheme 7) [14]. The above nitrone-thiazole methodology was also applied for the synthesis of novel anomeric Cglycosyl α-amino acids by oxidation of the corresponding α-amino aldehydes with NaClO 2 in aqueous NaH 2 PO 4 [24].…”
Section: Reactivitymentioning
confidence: 99%
“…In addition to the above mentioned synthesis of β-hydroxy-α-amino acids through the reaction of 2-furyllithium with aldose-derived nitrones outlined in Scheme 3, the furan-based methodology was also utilized for preparing both glycosyl α-amino acids and their N-hydroxy derivatives (Scheme 8) [24]. The FBAH methodology was used for the total synthesis of Polyoxin J 34, a peptidyl nucleoside antibiotic of interest as an inhibitor of chitin biosynthesis.…”
Section: Reactivitymentioning
confidence: 99%